Respostas
respondido por:
3
Fazendo o determinante temos:
sen2x.cosx-senx.cos2x=Sen(2x-x)=senx
(C)
sen2x.cosx-senx.cos2x=Sen(2x-x)=senx
(C)
respondido por:
2
Olá!
Relação fundamental da trigonometria : senx² + cos² = 1
sen2x = senx.cosx + cosx.senx = 2senx.cosx
cos2x = cosx.cosx - senx.senx = cosx² - senx².
2sex.cosx.cosx - (cosx² - senx²).senx
2senx.cosx² -cosx².senx + senx³
1senx.cosx² + senx³
senx.(1 - senx²) + senx²
senx - senx³ + senx³
senx
Resposta : C.
Relação fundamental da trigonometria : senx² + cos² = 1
sen2x = senx.cosx + cosx.senx = 2senx.cosx
cos2x = cosx.cosx - senx.senx = cosx² - senx².
2sex.cosx.cosx - (cosx² - senx²).senx
2senx.cosx² -cosx².senx + senx³
1senx.cosx² + senx³
senx.(1 - senx²) + senx²
senx - senx³ + senx³
senx
Resposta : C.
Anexos:
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás